Old dogs, new tricks: MR‐Linac training and credentialing of radiation oncologists, radiation therapists and medical physicists - Louise Hogan; Michael Jameson; David Crawford; Stacy Alvares; Conrad Loo; Maddison Picton; Zoe Moutrie; Claire Pagulayan; Ursula Jelen; Nicolle Dunkerley; Tania Twentyman; Jeremy deLeon; et al. (Journal of Medical Radiation Sciences, 2023)
Abstract The introduction of magnetic resonance (MR) linear accelerators (MR‐Linacs) into radiotherapy departments has increased in recent years owing to its unique advantages including the ability to deliver online adaptive radiotherapy. However, most radiation oncology professionals are not accustomed to working with MR technology. The integration of an MR‐Linac into routine practice requires many considerations including MR safety, MR image acquisition and optimisation, image interpretation and adaptive radiotherapy strategies. This article provides an overview of training and credentialing requirements for radiation oncology professionals to develop competency and efficiency in delivering treatment safely on an MR‐Linac.